Master tracks in different resolutions of HEINCKE cruise HE669, Bremerhaven - Bremerhaven, 2025-09-27 - 2025-10-09 - Matthias Brenner (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Heincke during expedition HE669 were processed to receive a validated master track which can be used as reference of further expedition data. During HE669 the inertial navigation system IXSEA PHINS III and the GPS receivers Trimble Marine SPS461 and SAAB R5 SUPREME NAV were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.